Transient thermal modeling of palsa distribution in Northern Norway, Finnmark And the importance of estimating local factors controlling palsa development. - Solheim, Ingvild (2016)
Palsas and peat plateaus are permafrost mounds situated in mires with a core of ground ice. In northern Norway, palsas are located in the sporadic permafrost zone, and demarcate the southernmost limit of permafrost. Thus these landforms are vulnerable to climate change. Polar Regions contain immense amounts of organic carbon frozen in the soil. Permafrost degradation in these areas leads to emission of greenhouse gasses and may further accelerate the climate feedback on hydrology, vegetation, infrastructure and climate. Permafrost models have proven to be sufficient tools in predicting the future scenario on ground temperatures and climate change. However, such models implement parameterizations on soil, vegetation and climate data which encompass broad uncertainties, as land cover and soil stratigraphy are estimated on a coarse scale and interpolated for large regions. Moreover, permafrost is controlled by local factors, which may vary over small scales. Therefore, sufficient datasets and parameter initializations are crucial in order to reproduce the state of the art- and future ground temperature regimes in permafrost regions. The grid based transient thermal model CryoGrid 2 has been forced with stratigraphy- and snow scenarios based on in situ measurements on both a local- and regional scale for palsa mires in Finnmark. The resulting ground temperatures and thaw depths are in surprisingly well agreement with in situ GSTs and active layer depth for the region, and validated against a recent map over the palsa distribution in Finnmark. The presented soil and snow scenarios may benefit permafrost models in improvement on parameters which are controlling the temperature regimes for permafrost in organic rich soil. Moreover, palsa distribution in Finnmark is strongly dependent on the insulating organic peat layer, and low snow depth throughout the winter in order to survive the current climate. The average thaw depth for the widely distributed study sites are comparable with one another and measured to be ...